Boron nitride foam as a polymer alternative in packaging phase change materials: Synthesis, thermal properties and shape stability. (15th March 2019) - Han, Weifang; Ge, Chunhua; Zhang, Rui; Ma, Zhiyan; Wang, Lixia; Zhang, Xiangdong
Graphical abstract: Boron nitride foam (BNF), as a ceramic material, can effectively solve the leakage issue and enhance thermal conductivity of phase change materials (PCMs). PCM/BNF exhibited higher latent heat, lower supercooling degree, better shape stability, thermal stability and reliability compared to EHS/polymer. Highlights: Three-dimensional porous boron nitride foam with high porosity was fabricated. The leakage of eutectic hydrated salt was prevented by boron nitride foam. Thermal conductivity of the composite was significantly enhanced. The composite exhibited shape stability, thermal stability and reliability. Abstract: The utilization of phase change materials (PCMs) for solar energy storage and industrial waste heat recovering is essential to protect the environment and build sustainable energy infrastructure in the coming years. The low thermal conductivity, leakage of the liquid-state and poor shape stability limited their broader application in energy conversion and storage. Here, construction of boron nitride foams (BNFs) is used as the packaging materials for PCMs. The BNFs with high porosity (∼97.6%) and low density (∼1.7 mg/cm 3 ) provide sufficient space for the adsorption of PCMs. Eutectic hydrate salt (EHS) is restricted in the pores of BNFs by the weak interactions which is proved by FTIR, XRD and Raman spectroscopy. In addition, the EHS/BNF composite PCMs exhibit low supercooling degree and high latent heat when compare with the EHS/polymer. Thermal conductivity of EHS/BNF composite PCMs with 4 wt% BNFs is 10.37 times higher than that of the pure PCMs and 2.24 times higher than for EHS/polymer. Especially, shape-stability and thermal reliability are still maintained after 100 thermal cycles. These results demonstrate that BNFs can be used as a promising candidate to replace polymers for energy conversion and storage field.